PRESTASI AKADEMIK SISWA BERKEBUTUHAN KHUSUS DI SEKOLAH DASAR INKLUSIF: PERAN KETERLIBATAN ORANG TUA DAN MEDIASI KETERAMPILAN SOSIAL - Citra Wahyuni; Frieda Maryam Mangunsong (Program Studi S1 Psikologi, 2022)
Student academic achievement is the result of the interaction between environmental factors and individual factors. This study uses parental involvement as environmental factors and social skills as individual factors that can affect the academic achievement of students with special needs in inclusive elementary schools. This study aims to examine the theoretical model of students' social skills as mediator on the effect of parental involvement on the academic achievement of students with special needs in inclusive elementary schools. Participants in this study were parents of students with special needs (N=365) who studied in inclusive public and private elementary schools in five areas of DKI Jakarta. The results showed that social skills mediate the effect of parental involvement on the academic achievement of students with special needs in inclusive primary schools.